Perbedaan Pengetahuan Remaja Putri Sebelum dan Sesudah Diberikan Pendidikan Kesehatan Melalui Media Video Tentang Deteksi Dini Kanker Payudara di Desa Ngampel Kulon Kecamatan Ngampel Kabupaten Kendal: Differences In Knowledge Of Adolescent Women Before And After Health Education Through Video Media About Early Detection Of Breast CancerIn Ngampel Kulon Village - Mutya Risty Mulyani; Puji Lestari (Journal of Holistics and Health Sciences (JHHS), 2022)
According to Global Burden Cancer data in the International Agency for Research On Cancer (IARC) it is known that breast cancer is a disease with the highest percentage of new cases (after controlling for age), which is 43.3%, and the percentage of deaths (after controlling for age) due to cancer. breast cancer by 12.9%. To prevent the occurrence of breast cancer, education through video is needed to be able to carry out early detection of breast cancer. The purpose of this study was to determine the difference in knowledge of young women before and after being given health education through video media about early detection of breast cancer themselves (BSE) in Ngampel Kulon Village. This study uses quantitative methods, the research design used is Quasy Experiment or, with a non-equivalent approach (pretest and posttest) control group design. The population is all young women in Ngampel Kulon Village, the sampling technique used is Purposive Sampling calculated using the Cohort formula so that 45 respondents are obtained. Research using the Wilcoxon test results that there is a difference in the mean value of knowledge before being given an intervention is 1.75 and after being given an intervention it becomes 1.75. 2.69 with p-value = 0.000 (α=0.05). This means that there is a difference in the knowledge of young women before and after being given health education through video media about early detection of breast cancer in Ngampel Kulon Village. Based on this research, it can be concluded that health education through video media can increase the knowledge of young women about early detection of breast cancer. ABSTRAK Menurut data Global Burden Cancer dalam International Agency For Research On Cancer (IARC) diketahui bahwa kanker payudara merupakan penyakit dengan presentase kasus baru (setelah dikontrol oleh umur) tertinggi, yaitu sebesar 43,3%, dan persentase kematian (setelah dikontrol oleh umur ) akibat kanker payudara sebesar 12,9%. Untuk mencegah terjadinya kanker payudara diperlukan edukasi melalui video agar mampu melakukan deteksi dini kanker payudara. Tujuan Penelitian ini adalah untuk mengetahui perbedaan pengetahuan remaja putri sebelum dan sesudah diberikan pendidikan kesehatan melalui media video tentang deteksi dini kanker payudara sendiri (SADARI) di Desa Ngampel Kulon. Penelitian ini menggunakan metode kuantitatif, desain penelitian yang digunakan adalah Quasy Experiment, dengan pendekatan non equivalent (pretest dan posttest) control group design. Populasi adalah semua remaja putri di Desa Ngampel Kulon, teknik sampling yang digunakan adalah Purposive Sampling dengan dihitung menggunakan rumus Kohort sehingga diperoleh responden sebanyak 45. Penelitian menggunakan uji Wilcoxon mendapatkan hasil bahwa terdapat perbedaan nilai rerata pengetahuan sebelum diberikan intervensi adalah 1.75 dan setelah diberikan intervensi menjadi 2.69 dengan nilai p-value = 0.000 (α=0.05). Hal ini berarti ada perbedaan pengetahuan remaja putri sebelum dan sesudah diberikan pendidikan kesehatan melalui media video tentang deteksi dini kanker payudara di Desa Ngampel Kulon. Berdasarkan penelitian ini dapat disimpulkan bahwa pendidikan kesehatan melalui media video dapat meningkatkan pengetahuan remaja putri tentang deteksi dini kanker payudara.